2022
DOI: 10.2337/dc22-1219
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Randomized Trial of Intermittently Scanned Continuous Glucose Monitoring Versus Self-Monitoring of Blood Glucose in Individuals With Type 2 Diabetes and Recent-Onset Acute Myocardial Infarction: Results of the LIBERATES Trial

Abstract: OBJECTIVE To analyze the impact of modern glucose-monitoring strategies on glycemic and patient-related outcomes in individuals with type 2 diabetes (T2D) and recent myocardial infarction (MI) and assess cost effectiveness. RESEARCH DESIGN AND METHODS LIBERATES was a multicenter two-arm randomized trial comparing self-monitoring of blood glucose (SMBG) with intermittently scanned continuous glucose monitoring (isCGM), also kn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Finally, 12 RCTs were included. Corresponding authors of the publications of all 12 RCTs were contacted to obtain any missing data, and the investigators of five RCTs [ 21 25 ] provided additional data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 12 RCTs were included. Corresponding authors of the publications of all 12 RCTs were contacted to obtain any missing data, and the investigators of five RCTs [ 21 25 ] provided additional data.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline HbA 1c ranged from a mean of 61.1 mmol/mol (7.83%) to 77.9 mmol/mol (9.27%) (Table 1 ). Eleven trials had a two-arm open-label parallel group design [ 21 31 ]. One trial had a three-arm parallel group design [ 32 ], including arms with 1 week of CGM use at baseline only (first arm), 1 week of CGM use at both baseline and at the end of the study period after 12 weeks (second arm) and a control arm that did not use CGM (third arm) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies evaluating the use of the fCGM in patients undergoing treatment with non-insulin antidiabetic agents or the combination with basal insulin reported statistically significant decreases in HbA1c levels compared to standard blood glucose self-monitoring. One of these studies also reported significant improvements in the Diabetes Self-Management Questionnaire (DSMQ) subscales, which include glucose management (p = 0.042), dietary control (p = 0.048), physical activity (p = 0.043), use of healthcare (p = 0.001), and self-care (p = 0.001), compared to baseline values [ 18 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to significant reductions in hypoglycemia, there has also been a demonstrable cost-effectiveness to utilizing CGM instead of FSBG in older adults. 25 The available data are promising, and trends of CGM use in older adults assessed from the Diabetes Prospective Follow-up Registry indicate that utilization of CGM in older adults is increasing. 26…”
Section: Overview Of Cgm Use In Older Adultsmentioning
confidence: 99%